View of the Chaturmukha linga from the south - Temples of India Project Team (Jio Institute, 2024)
On the south side of the linga, one can observe the face and bust of the deity. The deity has a heavy jatamukuta (matted crown) on its head and hairlocks coming down to the shoulders. The sringara (attributes) of all four faces of the Chaturmukha linga are distinct, highlighting the iconographic features.